Laryngeal amyloidosis. Issue 6 (December 2019) - Burns, Hannah; Phillips, Nicholas
Abstract : Purpose of review: Laryngeal amyloidosis is a rare hematological disorder of plasma cells. The cause is still considered idiopathic. The otolaryngology literature predominantly comprises case reports and short series. The present review summarizes the amyloid literature more generally in order to assist the otolaryngologist managing this disorder. Recent findings: Distinguishing localized amyloidosis from systemic disease continues to be challenging. Both radiological and hematological investigations may assist. Surgery continues to be the predominant modality for treatment, but radiation and potentially medical approaches are on the horizon. Summary: When localized, this benign laryngeal disease carries an excellent prognosis. Clinicians should however be aware of systemic presentations and ensure patients receive long-term follow-up.